Implementation of Cheapest Insertion Heuristic Algorithm in Determining Shortest Delivery Route - Fargiana, Farid; Respitawulan, Respitawulan; Fajar, Yusuf; Suhaedi, Didi; Harahap, Erwin (International Journal of Global Operations Research, 2022)
The buying and selling transaction system that many people use today is the online buying and selling system. In this system, there is a process of goods delivery by one branch of a freight forwarder in Indonesia, namely SiCepat Express Baleendah. In the process of shipping goods, a delivery route with the shortest path is needed in order to minimize of the goods delivery process. The problem of the route of goods delivery can be solved by one of the algorithms in the Traveling Salesman Problem (TSP), namely the Cheapest Insertion Heuristic (CIH) Algorithm. This study aims to determine the shortest route and distance for goods delivery using the CIH Algorithm by the Asymmetric TSP CIH application, as well as knowing its efficiency compared to the route that used by SiCepat Express Baleendah. The result shows that the use of the CIH Algorithm is proven to produce a more efficient delivery route than the route created by SiCepat Express Baleendah. Based on the goods delivery route from SiCepat Express Baleendah, the result of the total distance is 18.55 km. On the other hand, based on the CIH Algorithm, the delivery route obtained result is 13.45 km. The efficiency of using the CIH Algorithm is 27.48% better than the result from SiCepat Express Baleendah route.